PEMANFAATAN URIN MARM0T MENJADI PUPUK CAIR DI KAMPUNG SIBONGKOK KABUPATEN BOGOR - Fitriani, Neng Siska Fitriani; Hasanah, Tita (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
This service activity aims to utilize guinea pig urine into liquid fertilizer. The service method is service learning which involves school age children in Sibongkok Village, Curugbitung Village, Nangggung District, Bogor Regency. The activity period was carried out for one month. The activity stages are pre-service, implementation of service, and post-service. During the pre-service period, all participants did not know the benefits of guinea pig urine, then participants were given understanding and training to make fertilizer using guinea pig urine. After the service, it was observed that all participants were very enthusiastic about using guinea pig urine to make liquid fertilizer.